Molecular identification of uncommon clinical yeast species in Iran - Ladan Karimi; Hossein Mirhendi; Hossein Khodadadi; Rasoul Mohammadi (Mazandaran University of Medical Sciences, 2015)
Background and Purpose: By using advanced detection/identification methods, the list of emerging uncommon opportunistic yeast infections is rapidly expanding worldwide. Our aim in the present study was sequence-based species delineation of previously unidentified yeasts obtained from a clinically yeast collection. Materials and Methods: A total of twenty three out of the 855 (5.7%) yeast isolates which formerly remained unidentified by PCR-RFLP method, were subjected to sequence analysis of the entire internal transcribed spacers (ITS) regions of rDNA. The precise species recognition was performed by the comparison of the sequences with the reliable GenBank database. Results: Sequencing analysis of the ITS region of the strains revealed several uncommon yeasts that were not reported previously in Iran. The species include Hanseniaspora uvarum, Saccharomyces cerevisiae, Sporidiobolus salmonicolor, Pichia fabianii, Pichia fermentans, Candida famata, Candida inconspicua, Candida maqnoliae, Candida guilliermondii, Candida kefyr, Candida rugosa, Candida lusitaniae, Candida orthopsilosis, and Candida viswanathii. Conclusion: We identified several rare clinical isolates selected from a big collection at the species level by ITS-sequencing. As the list of yeast species as opportunistic human fungal infections is increasing dramatically, and many isolates remain unidentified using conventional methods, more sensitive and specific advanced approaches help us to clarify the aspects of microbial epidemiology of the yeast infections.